EFEKTIVITAS INSEKTISIDA DALAM MENEKAN PERKEMBANGAN POPULASI DAN SERANGAN LIRIOMYZA, SP PADA TANAMAN BAWANG MERAH LOKAL PALU (Allium cepa L.x Wakegi Araki) DI DESA GUNTARANO KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Arfan Arfan; Sri Sudewi; Mihwan Sataral; Sumarni Sumarni; Vevi Rosiani; Mumfahida Mumfahida; Karmila Soar (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2018)
This study aimed to examine the effectiveness of some insecticides on the population development and attack Liriomyza sp on local Palu onions. The research conducted from Februari to April 2017, at Guntarano village, Tanantovea Sub-District, Donggala District. The study used Randomized Block Design (RAK) consisting of four treatments, namely Po.Control; P1. Abamectin; P2. Azadiractin; P3. Dimohipo. Each treatment was repeated three times so that 12 treatments were obtained. The results showed that the insecticidal treatment had an effect on the development of the varied Liriomyza sp. Adult population at various plant age levels. Observations on plant age 5 and 6 of MST showed that abamectin insecticides were effective in suppressing the growth larvae populations of Liriomyza sp compared with the treatment of Azadiractin, Dimohipo and non-treated insecticides.